Food wars! shokugeki no soma. volume 16, Captured queen - Tsukuda, Yuto, 1989- (Shonen Jump advanced., 2017)
Day three of the Autumn Moon Festival has begun, and Soma is still trying to recover from ending deep in the red on its first day. Looking to finally overtake Restaurant Kuga in overall profit, Soma unveils his ace in the hole--a new mapo tofu recipe! Will it be enough to push this first-year to victory over a Council of Ten member?